101k views
3 votes
Simplify the expression below by applying the zero exponent rule. (5-8)^0 = Answer

Simplify the expression below by applying the zero exponent rule. (5-8)^0 = Answer-example-1
User Mstfdz
by
5.7k points

1 Answer

4 votes

Zero Exponent Rule:


\begin{gathered} a^0=1 \\ a\\eq0 \end{gathered}

Thus, anything to the power of 0 is "1", except 0.

Let's simplify the expression shown:


\begin{gathered} (5-8)^0 \\ =(-3)^0 \\ =1 \end{gathered}Answer1
User Roberto Trani
by
4.9k points